2009
DOI: 10.1136/oem.2008.045542
|View full text |Cite
|
Sign up to set email alerts
|

Long-term exposure to traffic-related air pollution and mortality in Shizuoka, Japan

Abstract: Long-term exposure to traffic-related air pollution, indexed by nitrogen dioxide concentration, increases the risk of cardiopulmonary mortality, even in a population with a relatively low body mass index and increases the risk of lung cancer mortality in non-smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
42
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 31 publications
4
42
5
Order By: Relevance
“…Several case-control and cohort studies with adequate adjustment for smoking and other potential confounding factors similarly indicated higher risks for lung cancer in association with different measures of air pollution (1)(2)(3)(4)(5)(6)(7)(8). Not all the previous studies showed significant associations and not all showed associations for the same pollutants (or proxies); furthermore, the magnitude of the risk estimates differed.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Several case-control and cohort studies with adequate adjustment for smoking and other potential confounding factors similarly indicated higher risks for lung cancer in association with different measures of air pollution (1)(2)(3)(4)(5)(6)(7)(8). Not all the previous studies showed significant associations and not all showed associations for the same pollutants (or proxies); furthermore, the magnitude of the risk estimates differed.…”
Section: Introductionmentioning
confidence: 79%
“…Nevertheless, the overall picture is a modestly increased risk for lung cancer in association with various measures of exposure to air pollution. Furthermore, several studies have indicated that the effects of air pollution on the risk for lung cancer might be modified by smoking status, such that an effect is strongest or detectable only among nonsmokers or never smokers (3,4,7,8). Other factors have also been suggested to modify the effect of air pollution, for example, fruit consumption (7), gender, and educational level (3).…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be noted that 2 cohort studies examining stroke mortality and a case-control study examining hospital admissions for ischemic stroke did not find any significant associations with outdoor air pollution concentrations. 11,12,26 A further cohort study examining stroke mortality found no evidence of association with outdoor background pollution concentrations but did observe a significant association with road traffic exposure. 27 In an ecological study carried out in Edmonton, Canada, Johnson et al found no significant associations between a range of air pollutants and ischemic or hemorrhagic stroke after adjustment for area-level deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 In contrast, although there is an increasing number of studies examining the effects of chronic exposure to outdoor air pollution on cardiovascular mortality using cohort study designs, 10 few have specifically examined stroke mortality. 11,12 Studies examining mortality, however, are unable to distinguish between the effects of an exposure on incidence of a disease and the effects of the exposure on survival after development of the disease and we have recently found that outdoor air pollution has a substantial adverse effect on survival after stroke. 13 To date, only 1 cohort study has examined the effects of outdoor air pollution on incidence of stroke and an increase in incidence associated with increasing levels of particulate matter Ͻ2.5 m in diameter (PM 2.5 ) was observed.…”
mentioning
confidence: 99%
“…It concluded that there are inconsistencies in the existing data and that there is insufficient evidence of an association between local traffic-related pollution and COPD. Since both reviews have been published, a number of new publications have emerged [11][12][13][14][15][16]. In the light of these, the objective of this review is to reassess the epidemiological evidence for a role of long-term exposure to the complex mixture of outdoor air pollution in the development of objectively defined COPD.…”
Section: Introductionmentioning
confidence: 99%